Analysis Of Factors Affecting Firm Value (Empirical Studies On Food And Beverage Sub-Sector Industry Companies Listed On Idx In 2014 – 2020) - Melati Dwi Nabila Putri; Zainul Kisman (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2022)
This study aims to determine the effect of profitability, dividend policy, firm size, and debt policy on firm value in the Manufacturing sector of the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) in 2014-2020. The ratios used in this study include Price to Book Value (PBV), Return on Equity (ROE), Dividend Payout Ratio (DPR), Log Total Assets, and Debt to Equity Ratio (DER). This study used 10 companies as research samples with 7 years of observation, resulting in 70 observations. This research uses Eviews version 10 program with panel data analysis method. The method used in sampling in this study, namely purposive sampling technique. The results showed that simultaneously profitability (ROE), Dividend Policy (DPR), Firm Size (Log Total Assets), and Debt Policy (DER) variables had an effect on firm value, and partially Profitability (ROE) and Debt Policy (DER) variables. has a positive and significant effect on firm value. Then the Dividend Policy (DPR) has a negative and significant effect on firm value. While Firm size (Log Total Assets) has no effect on firm value in the company